O Teorema de Bohnenblust-Hille - Alarcón, Daniel Núñez (2011)
The Bohnenblust-Hille Theorem, proved in 1931 in the prestigious journal Annals of Mathematics, asserts that if U : lN 1 ----- lN 1 --! K is an n-linear form and N is a positive integer N, then 0@ N X i1;:::;in=1 jU(ei1 ; :::; ein)j 2n n+11A n+1 2n - Cn kUk , with Cn = n n+1 2n 2 n--1 2 . After a long time overlooked, this result has been explored in the recent years. In this work we detail a beautiful proof of the Bohnenblust-Hille Theorem, due to A. Defant, U. Schwarting and D. Popa. We also investigate the estimates of the constants involved and some asymptotic information, following a recent work of D. Pellegrino and J. Seoane-Sepúlveda.